Cave of bones [compact disc, unabridged] : a Leaphorn, Chee & Manuelito novel - Hillerman, Anne, 1949- (Hillerman, Tony, Leaphorn and Chee novel, 2018)
When Tribal Police Officer Bernadette Manuelito arrives to speak at an outdoor character-building program for at-risk teens, she discovers chaos. Annie, a young participant on a solo experience due back hours before, has just returned and is traumatized. Gently questioning the girl, Bernie learns that Annie stumbled upon a human skeleton on her trek. While everyone is relieved that Annie is back, they're concerned about a beloved instructor who went out into the wilds of the rugged lava wilderness bordering Ramah Navajo Reservation to find the missing girl. The instructor vanished somewhere in the volcanic landscape known as El Malpais. In Navajo lore, the lava caves and tubes are believed to be the solidified blood of a terrible monster killed by superhuman twin warriors.